The Business Performance of New Technology-based Firms: The Importance of the Business Model's Value Proposition and Customer Relationships - Löfsten, Hans (Senate Hall, 2019)
This study analyses the impact of the business model's value proposition and customer relationships on business performance of new technology-based firms (NTBFs). NTBFs must create a suitable business model to commercialise a new product or service to realize their economic potential and perform as a business. We conducted a survey among 401 small, young Swedish NTBFs in 2016 in the early stages of their existence and applied a multiple regression analysis explaining business performance from various measures capturing value propositions and customer relationships. The results show that performance-enhancing elements for business performance in the early phases are product similarity (to products of other firms), internationalisation and maintaining very close relationships to customers. The finding on product similarity is particularly striking as it suggests that in the early stages of NTBFs it is imitation rather than innovation that may help achieve higher business performance. This study contributes to the literature on NTBFs by showing how various elements of the business model's value proposition and customer relationships affect the firm's business performance in the very early stage of its development.
Keywords: value proposition|customer relationships|business performance|business model|new technology-based firms